Pembuatan Website Pesantren sebagai Sarana Informasi dan Promosi Toko Swalayan Qismart - Taufikurrahman Taufikurrahman; Rachmadhany Iman; Ahmad Haikal Nuqqy Zahhar (Router : Jurnal Teknik Informatika dan Terapan, 2024)
The creation of the website of MaQis Alhamidy 4 Islamic Boarding School aims to provide an effective means of information and promotion to support the Qismart self-service store managed by the pesantren. In today's digital era, the existence of a website is very important for organizations, including Islamic educational institutions such as Pondok Pesantren MaQis Alhamidy 4. This website is designed not only to convey information about pesantren activities and services, but also to promote the pesantren self-service which serves as one of the main sources of income. Website development is carried out through several stages, namely observation, identification, implementation, and evaluation. The KKN Inovasi Pesantren Group 02 team, consisting of 16 members, was directly involved in this process. In the observation stage, the team observed and recorded the phenomena that occurred in the pesantren. Problem identification was conducted through interviews with pesantren administrators to understand the needs and challenges faced, especially related to the self-service information and promotion system. The implementation stage involved information collection and assistance in using the website as an information medium. Evaluation was conducted to reflect on the process and results achieved. The results of this project show that the developed website successfully created an effective platform to introduce and promote Qismart Supermarket to the community. The website facilitates access to important information and strengthens the brandi.